The Future of the Non-Proliferation Treaty
XIV, 226 p.
Keywords: In 1995 a Conference is to be convened to review and extend the Treaty on the NonProliferation of Nuclear Weapons (NPT). The Future of the NPT brings together a distinguished group of individuals, including the elected President of the 1995 NPT Conference, to analyse four crucial agenda areas relevant to the Conference: the preConference activities to be undertaken by both States Parties and the Conference Secretariat; those security issues that relate to a review of the treaty, such as nuclear disarmament and security assurances; peaceful uses and verification questions; and regional issues. With nuclear nonproliferation currently occupying a prominent position on the international security agenda, the 1995 Conference offers a unique opportunity for a constructive discussion on these areas and it is hoped that this volume will provide a contribution to that end.